The hepatic innate immune response is lobe-specific in a murine model endotoxemia. Issue 2 (February 2019) - Nguyen, Leanna; Sandoval, Jeryl; De Dios, Robyn; Yihdego, Elesa; Zarate, Miguel; Castro, Odalis; McKenna, Sarah; Wright, Clyde J
The liver plays a central role in the innate immune response to endotoxemia. While previous studies have demonstrated lobe-specific transcriptional responses to various insults, whether this is true in response to endotoxemia is unknown. We sought to assess whether there were significant intra- and inter-lobe differences in the murine hepatic innate immune transcriptional response to endotoxemia. Adult male ICR mice were exposed to i.p. LPS (5 mg/kg, 30 min, 60 min, 5 h) and primary ( Tnf, Cxcl1, Nfkbia, Tnfiap3) and secondary ( Il6, Nos2 ) innate immune response gene expression was assessed in the left medial, right medial, left lateral, and right lateral lobes, and the papillary and caudate processes. The expression of all innate immune response genes increased following i.p. LPS challenge. When tested at the early time points (30 and 60 min), the left medial lobe and caudate process consistently demonstrated the highest induction of gene expression. Most inter-lobe differences were attenuated at later time points (5 h). To improve reproducibility of the study of endotoxemia induced by i.p. LPS challenge, inclusion of appropriate methodological details regarding collection of hepatic tissue should be included when reporting scientific results in published manuscripts.